Micro-ballistic response of thin film polymer grafted nanoparticle monolayers - Pal, Subhadeep; Keten, Sinan (Soft matter, 2024)
Self-assembled polymer grafted nanoparticles (PGNs) are of great interest for their potential to enhance mechanical properties compared to neat polymers and nanocomposites. Apart from volume fraction of nanoparticles, recent experiments have suggested that nanoscale phenomena such as nanoconfinement of grafted chains, altered dynamics and relaxation behavior at the segmental and colloidal scales, and cohesive energy between neighboring coronas are important factors that influence mechanical and rheological properties. How these factors influence the mechanics of thin films subject to micro-ballistic impact remains to be fully understood. Here we examine the micro-ballistic impact resistance of PGN thin films with polymethyl methacrylate (PMMA) grafts using coarse-grained molecular dynamics simulations. The grafted chain length and nanoparticle core densities are systematically varied to understand the influences of interparticle spacing, cohesion, and momentum transfer effects under high-velocity impact. Our findings show that the inter-PGN cohesive energy density ( γ PGN ) is an important parameter for energy absorption. Cohesion energy density is low for short grafts but quickly saturates around entanglement length as adjacent coronas interpenetrate fully. The response of γ PGN positively influences specific penetration energy, , which peaks before chain entanglement starts (< N e ). We further divide the ballistic response into three regimes based on grafted chain length: short graft, intermediate graft, and entangled graft. The short grafted PGNs show fragmentation due to almost no cohesion between particles, and the rigid body motion of the nanoparticles absorbs most of the energy. When chains are in the intermediate graft length regime, the film fails by chain pull-out, and unraveling of grafts is the primary dissipation mechanism. The Ashby plot of penetration energy, E p , indicates ballistic processes are inelastic collisions when grafted chains are short and vary with density in a power law fashion as expected from momentum transfer. The response indicates that a lower nanoparticle weight fraction, wt NP , leads to higher energy absorption per mass, that is, the added mass of nanoparticles does not warrant proportionate increases in energy absorption in the parametric range studied. However, the peak deceleration, A b , shows a clear positive effect of adding NPs. Finally, PGNs with intermediate chain lengths simultaneously show relatively higher and A b . μ-Ballistic simulations performed on the PGN thin films reveal a positive influence of cohesive energy density on the performance. PGN with heavier nanoparticles arrest bullets more rapidly, however, lighter particles exhibit a higher .